It ́s not Porno, Ladies and Gentlemen, it ́s Sex-fiction: a Critical Look at “Modernity” in 1970s Cali, Colombia in Aventuras de un impotente [Adventures of an Impotent Man] by Hernán Hoyos (2016)
This article aims at showing the way in which the sex-fiction novel Aventuras de un impotente [Adven- tures of an impotent man] by Hernán Hoyos questions the “modernity” of the bourgeois class in Cali, Colombia during the 1970s; a kind of modernity constituted in reference to the United States. This study also contextualizes the work of Hoyos and presents a reflection on the category “sex-fiction”, created by the author to refer to his own works, which have been scarcely discussed in academic circles.